Endocannabinoid system in periodontitis: A systematic review and in silico analyses - Soares, Lélio Fernando Ferreira [UNESP]; Oliveira, Jovânia Alves; Nogueira, Andressa Vilas Boas; Júnior, Carlos Rossa [UNESP]; Pigossi, Suzane Cristina; Deschner, James; Cirelli, Joni Augusto [UNESP] (Elsevier, 2025)
OBJECTIVE: This systematic review with in silico investigation discusses the involvement of the endocannabinoid system (ECS), particularly CB1 and CB2 receptors (genes CNR1 and CNR2 respectively), in periodontal health and disease (PD). METHODS: PubMed/MEDLINE, Embase, Web of Science, Scopus, and The Cochrane Library databases were searched for studies on periodontitis and ECS published up to August 2024. The GSE16134 dataset was used for analyses of differential gene expression, correlation of ECS genes, evaluation of biomarkers and functional enrichment analysis. RESULTS: Nine studies met the inclusion criteria (three clinical and six preclinical studies). Clinical studies demonstrated that CNR2 gene expression was significantly reduced in periodontitis, while CNR1 showed minor changes. Animal studies with CB2 activation by different therapies increased receptor expression, reduced pro-inflammatory cytokines, and mitigated alveolar bone loss. CB1 activation also reduced inflammation and bone loss. Anandamide (AEA), an endogenous ligand of the cannabinoid receptors, exhibited anti-inflammatory effects, with endogenous levels decreasing after therapy. Bioinformatics analysis revealed that CNR1 expression in PD tissues was positively associated with genes involved in B-cell activation and humoral immune responses. In contrast, CNR2 expression showed strong correlations with genes related to immune regulation and extracellular matrix remodeling, suggesting distinct yet complementary roles for CB1 and CB2 in periodontal inflammation. CONCLUSIONS: The ECS participates in periodontal inflammation, with CB2 activation emerging as a promising therapeutic target.